Distribution and Fractionation of Heavy Metals in Sediments of Karra River, Hetauda, Nepal - Pradhanang, Sadhana (Journal of Institute of Science and Technology, 2015)
A five-step sequential extraction procedure was applied for the determination of the distribution of four elements (Cr, Mn, Fe, and Ni) in sediment of the Karra River. Sediment samples were collected from 16 different sites in the Karra River (upstream, industrial belt, downstream). The distribution of trace metals among exchangeable, carbonate, reducible, oxidizable and residual fractions were determined. The total concentration of metals varies in the range of Cr 72–4339.54 mg kg?1, Mn 22–411.93 mg kg?1, Fe 2967.23-32423.0 mg kg?1 and Ni 31.70-180.74 mg kg?1. The accuracy evaluated by comparing total trace metal concentrations with the sum of the five individual fractions proved to be satisfactory. The chemical speciation of Cr, Mn, Fe, and Ni in most sampling stations were in the order of residual > reducible > oxidazable > carbonate> exchangeable. Fractionation analysis showed that dominant metals are in residual fraction. The highest metal concentrations were observed at the most polluted sites of the industrial belt. High concentration of chromium was found in the Fe-Mn oxide and organic fraction in some of the sites of industrial belt. Journal of Institute of Science and Technology, 2014, 19(2): 123-128